Manajemen Berbasis Sekolah dalam Pendidikan Islam: Implementasi, Tantangan, dan Integrasi Nilai - Epy Pujiaty; Esa Lara Mardes (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the implementation of School-Based Management (SBM) in Islamic educational institutions through a literature review approach. The research aims to analyze its conceptual foundation, implementation practices, challenges, and the integration of Islamic values. SBM represents a decentralization model that grants autonomy to schools in managing curriculum, human resources, and financial systems. The findings indicate that SBM enhances stakeholder participation, teacher commitment, and institutional accountability, particularly when supported by visionary leadership and structured management. However, challenges remain, including limited managerial capacity, weak financial transparency, low community involvement, and resource disparities. The integration of Islamic values such as amanah, shura, and maslahah strengthens the ethical and spiritual dimensions of school governance. This study contributes to the literature by offering a synthesized conceptual framework that positions the integration of Islamic values not merely as complementary, but as an intrinsic dimension shaping the operationalization of SBM within Islamic educational contexts. The study recommends strengthening managerial competencies, improving transparency, and developing evidence-based policies to ensure sustainable and effective SBM implementation.